The CD177 c.1291A Allele Leads to a Loss of Membrane Expression and Mimics a CD177-Null Phenotype - Traum, Annalena; Jehle, Stefanie; Waxmann, Yannick; Litmeyer, Anne-Sophie; Berghöfer, Heike; Bein, Gregor; Dammann, Reinhard; Perniss, Alexander; Burg-Roderfeld, Monika; Sachs, Ulrich J.; Bayat, Behnaz; Justus Liebig University Giessen (My University, 2024)
CD177 is a glycosyl phosphatidyl inositol (GPI)-linked, neutrophil-specific glycoprotein that in 3–5% of normal individuals is absent from all neutrophils. The molecular mechanism behind the absence of CD177 has not been unravelled completely. Here, we analyse the impact of the recently described CD177 c.1291G>A variant on CD177 expression. Recombinant CD177 c.1291G>A was expressed in HEK293F cells and its expression on the cell surface, inside the cell, and in the culture supernatant was investigated. The CD177 c.1291G>A protein was characterised serologically and its interaction with proteinase 3 (PR3) was demonstrated by confocal laser scanning microscopy. Our experiments show that CD177 c.1291G>A does not interfere with CD177 protein biosynthesis but affects the membrane expression of CD177, leading to very low copy numbers of the protein on the cellular surface. The mutation does not interfere with the ability of the protein to bind PR3 or human polyclonal antibodies against wild-type CD177. Carriers of the c.1291G>A allele are supposed to be phenotyped as CD177-negative, but the protein is present in soluble form. The presence of CD177 c.1291A leads to the production of an unstable CD177 protein and an apparent “CD177-null” phenotype.
Keywords: ddc:610